Selected Liver Markers in Predicting the Severity of Organophosphate and Carbamate Poisoning - Senarathne, R.; Hettiaratchl, U.; Athiththan, L.; Peiris, H.; Sarathchandra, C.; Senanayake, H. (Hindawi, 2022)
Backgrounil. Intentional ingestion of organophosphate (OP) and carbamate is a significant health issue worldwide. It causes adveise health effects on the liver. This study aimed to determine liver transaminases (AST and ALT) and bilirubin levels to assess the severity of poisoning in patients with acute OP and carbamate poisoning. Melhods. A descriptive cross-sectional study was colducted on patients ,.trol[..] to a selected hospital in Sri Lanka with acute OP and carbamate poisoning. 'Ile severily of poisoning *us.1n"uro.ed by RBC cholinesterase and Peradeniya Organophosphorus Poisoning scale (POP), where six clinical ^features iere assessed based on a 3-point scaie. A score of0-3 was considered mild,4-7 to be moderate, and 8-l I to be severe poisoning. Liver parameters such as AST, ALT, and total and direct bilirubin were measured. Results. Among the 188 screened patients, i66 were recruited. Majority were male s (1I2,67.5o/o). Kruskal-Wallis test showed significant differences in ASTand ALT on admission and AST on discharge, across POP groups ((X' Q, n = 166) = 26.48, P < 0.001), (X' Q, n = 166) = 14.31, P = 0.001)' ard (X2 (2, n - 157) = tt.34, p = o.oo:1, respectively)). Mann-Whitney U test showed signifcantly frighle_S] 1nd ALT in the modeiate POP group compared to the mild POP group (AST: U= 1709, z= -4.50, p < 0.001, r = 0.36; ALT: U = 2ll4' z = -3.04, p=O.OO2, r=O-lS) Ln admission. In addition, the treatment outcomes (duration of hospital stay and duration of ventilator assistance) were significantly correlated (p<0.001) with the severity of poisoning and serum AST and ALT at the time of admission. Concluiion. AST anil ALT leveis on admission ancl AST level at discharge showed significant correlations with the severity of poisoning. Treatment outcomes significantly correlated with the severity of poisoning and serum AST and ALT levels'